Ethanol extract of propolis-bovine bone graft combination as a prospective candidate for socket preservation: Enhancing BMP7 and decreasing NFATc1 - Utari Kresnoadi; Jennifer Widjaja; Harry Laksono (Elsevier, 2021)
Objective: To analyse the expression of BMP7 in osteoblasts and NFATc1 in osteoclasts during the bone healing process in the extraction socket and the possible relationship between the expression of BMP7 and NFATc1. Methodology: This study represented a post-test only control group design consisting of four groups, namely; a control group (polyethylene glycol), an ethanol extract of propolis (EEP) group, a bovine bone graft (BBG) group, and a EEP-BBG group. 56 Cavia cobaya were split randomly into four groups. The mandibula left incisors of the subjects were extracted, treated with certain materials according to their group, and sutured. The expression of BMP7 and NFATc1 was observed on day 7 and day 14 by means of immunohistochemical staining. Statistical analysis was performed using a combination of one-way ANOVA, Games-Howell post-hoc, and Pearson tests. Results: The propolis-BBG combination group showed the highest BMP7 expression, on both day 7 and day 14. With regard to NFATc1 expression, the combination group experienced the lowest expression on day 7 and day 14. The combination group showed significant differences in all expressions compared to the control group. The BMP7 and NFATc1 expressions showed a strong relationship (r = -0.598, r > 0.5) Conclusion: Propolis-BBG combination increases BMP7 expression and reduces NFATc1 expression in the extraction socket. This study confirmed a strong relationship between the expressions of BMP7 and NFATc1.